Integrative-Based Nahwu and Kitabah Teaching Materials: An Innovative Model for Masdarul Ulum Islamic Boarding School - Imron, Kristina; Nurani, Qoim; Jibril, Muhammad; Abdullah, Muhammad Yahya (LISANIA: Journal of Arabic Education and Literature, 2025)
This study aims to develop an integrated teaching material that combines Kitabah (writing skills) and Nahwu (Arabic grammar), seeking to enhance students' understanding of Arabic grammar and writing skills. The background of this research lies in the separation between Nahwu and Kitabah learning, which has led to difficulties for students in applying grammar rules in writing at the twelfth grade of Pondok Pesantren Masdarul Ulum. Therefore, there is a need for teaching materials that integrate these two aspects to bridge the gap. This research employs the Research and Development (R&D) method with the Borg and Gall model, consisting of six stages: potential and problem analysis, data collection, product design, product validation, product revision, and product testing. The results of the study show that the developed teaching material is effective, as evidenced by a significant difference between the students' pre-test and post-test scores, with a Sig. (2-Tailed) value of 0.000, which is less than 0.05, indicating a significant improvement in students' writing skills and understanding of Nahwu after using this integrated teaching material. This research contributes to the development of more applicable and contextual Arabic teaching materials, emphasizing the integration of theory and practice in Arabic language learning.